Irisin is expressed by undifferentiated spermatogonia and modulates gene expression in organotypic primate testis cultures. (15th March 2020) - Wahab, Fazal; Drummer, Charis; Mätz-Rensing, Kerstin; Fuchs, Eberhard; Behr, Rüdiger
Abstract: The molecular mechanisms regulating undifferentiated spermatogonial cell proliferation and differentiation are still not fully understood. Irisin is an exercise-induced hormone, which is a cleaved and secreted fragment of the fibronectin type III repeat containing 5 (FNDC5) transmembrane protein. Recent studies have demonstrated the role of irisin in cell proliferation and differentiation in various tissues. However, testicular irisin expression and its potential action have not been analyzed. Here, we demonstrate expression of irisin in undifferentiated spermatogonia of primates and in the tree shrew, a bridging species between primates and insectivores. Rhesus monkeys are seasonal breeders with annual phases of high and low testicular activity and germ cell proliferation. Interestingly, expression of both FNDC5 mRNA and irisin is altered between breeding (high spermatogenesis) and nonbreeding seasons (low spermatogenesis). Organotypic testis culture in the presence of irisin increased the expression levels of the Sertoli cell ( GDNF ) and spermatogonial transcripts Kruppel-like factor 4 (KLF4), Inhibitor of differentiation 4 ( ID4 ), Cluster of differentiation 117 (cKIT), and SALL4, compared to untreated controls, while irisin suppressed its own FNDC5 mRNA. Our data suggest that irisin is a novel endocrine factor involved in the regulation of spermatogonial activities in the testes of primates. Highlights: Irisin is an exercise-induced hormone. Irisin expresses in primate testis on undifferentiated spermatogonia. Expression of both FNDC5 mRNA and irisin is altered between breeding and nonbreeding seasons. Irisin increased the expression levels of the Sertoli cell and spermatogonial transcripts in organotypic testis culture. Irisin is a novel factor involved in the regulation of spermatogonial activities.